The Analysis Study of Efficacy and Safety of Topical Anesthetic Agent for Treatment of Premature Ejaculation: A Comprehensive Systematic Review - Nugraha, Dhimas Mohammad Fajar; Akmalia, Tsalitsa Laili (International Medical Journal Corp. Ltd, 2024)
Background: Premature ejaculation (PE) affects 20-30% of men globally, with lifelong and acquired types requiring diverse behavioral and pharmacological treatments. This systematic review aims to analyze current evidence on the efficacy and safety of topical anesthetic agent for treatment of premature ejaculation based on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) six relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Overall, the evidence suggests that topical anesthetic agents are effective in treating PE. These agents consistently improve IELT and patient satisfaction, with a favorable safety profile. The findings also highlight the importance of individualized treatment approaches, considering patient preferences, sexual habits, and the specific characteristics of PE.